A new species of Hyalinobatrachium (Anura: Centrolenidae) from the Amazonian slopes of the central Andes, with comments on the diversity of the genus in the area - Castroviejo-Fisher, Santiago; Padial, José M.; Chaparro, Juan C.; Aguayo, Rodrigo; de La Riva, Ignacio (Zootaxa, 2009)
We describe a new species of Hyalinobatrachium from the Amazonian slopes of the Andes in Peru and Bolivia on the basis of morphological, bioacoustic and genetic characteristics. Hyalinobatrachium carlesvilai sp. nov. can be distinguished from other species of Hyalinobatrachium by the combination of the following characters: (1) truncate snout in dorsal and lateral view; (2) white pericardium; (3) enameled dorsal, tarsal and cloacal folds; (4) hand webbing formula III 2 – – 1 + IV; (5) iris cream; (6) advertisement call consisting of a single, frequency-modulated note with a pulsed section followed by a tonal section. The new species had been previously identified as Hyalinobatrachium munozorum and H. bergeri. The advertisement call of the new species was previously assigned to H. bergeri. Here we describe the previously unknown call of Hyalinobatrachium bergeri. Additionally, we study the taxonomic status of H. lemur and H. pellucidum and place the former as synonym of the later. We extend the distribution of H. pellucidum to Departamento Cusco in southern Peru.